2017
DOI: 10.1016/j.fertnstert.2016.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic grading of euploid blastocysts influences implantation and ongoing pregnancy rates

Abstract: Contrary to prior published studies, the current data suggest that blastocyst morphologic grading and particularly inner cell mass grade is a useful predictor of OPR per euploid embryo. Morphologic grading should be used to help in the selection among euploid blastocysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
93
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(120 citation statements)
references
References 27 publications
(62 reference statements)
12
93
0
4
Order By: Relevance
“…In a total of 417 cryopreserved embryo transfer cycles, excellent quality embryos (n = 38 [84.2%]) yielded a statistically significantly higher ongoing pregnancy rate compared with poor quality (n = 106 [35.8%]) and average quality (n = 197 [55.8%]) embryos (adjusted OR 11.0, 95% CI 3.8 to 32.1 and adjusted OR 4.8, 95% CI 1.7 to 13.3, respectively); good-quality embryos (n = 76) were associated with a statistically significant higher ongoing pregnancy rate than poor-quality embryos (61.8% versus 35.8%; P < 0.01). The authors also reported that inner cell morphology was a better predictor of pregnancy outcome than trophoectoderm morphology or blastocoel expansion (Irani et al, 2017). Concordant with this study, we, in our series, reported an overall effect of blastocyst morphology on ongoing pregnancy as depicted by linearby-linear association ( Table 3).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In a total of 417 cryopreserved embryo transfer cycles, excellent quality embryos (n = 38 [84.2%]) yielded a statistically significantly higher ongoing pregnancy rate compared with poor quality (n = 106 [35.8%]) and average quality (n = 197 [55.8%]) embryos (adjusted OR 11.0, 95% CI 3.8 to 32.1 and adjusted OR 4.8, 95% CI 1.7 to 13.3, respectively); good-quality embryos (n = 76) were associated with a statistically significant higher ongoing pregnancy rate than poor-quality embryos (61.8% versus 35.8%; P < 0.01). The authors also reported that inner cell morphology was a better predictor of pregnancy outcome than trophoectoderm morphology or blastocoel expansion (Irani et al, 2017). Concordant with this study, we, in our series, reported an overall effect of blastocyst morphology on ongoing pregnancy as depicted by linearby-linear association ( Table 3).…”
Section: Discussionsupporting
confidence: 91%
“…They reported similar ongoing implantation rates after SEBT of excellent (n = 110 [49.1%]), good (n = 32 [59.4%]), average (n = 60 [43.3%]) and poor (n = 13 [53.8%]) morphology blastocysts. A recent study, however, refuted these findings and reported that blastocyst morphology was still an independent predictor of ongoing pregnancy in PGS cycles (Irani et al, 2017). In a total of 417 cryopreserved embryo transfer cycles, excellent quality embryos (n = 38 [84.2%]) yielded a statistically significantly higher ongoing pregnancy rate compared with poor quality (n = 106 [35.8%]) and average quality (n = 197 [55.8%]) embryos (adjusted OR 11.0, 95% CI 3.8 to 32.1 and adjusted OR 4.8, 95% CI 1.7 to 13.3, respectively); good-quality embryos (n = 76) were associated with a statistically significant higher ongoing pregnancy rate than poor-quality embryos (61.8% versus 35.8%; P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, although this ratio cannot be implemented in a clinical setting, the morphological grading of ICM and TE is linked with embryo ploidy [40] and impacts on blastocyst potential even in euploid blastocysts [41].…”
Section: Resultsmentioning
confidence: 99%
“…It is known that factors such as embryo quality, maternal age, the patient's genetic background, clinical diagnosis, and treatment-related characteristics can affect pregnancy outcome 25,26 . Because embryo quality is one of the most important of these factors, the ultimate aim of any embryo-assessment approach is to identify embryos that have the highest implantation potential, resulting in live birth 24,27,28 .…”
Section: Predicting Pregnancy Likelihood Using the Trained Algorithm mentioning
confidence: 99%